Learning and teaching academic standards project : arts, social sciences and humanities : History : learning and teaching academic standards statement. - Hay, Iain (Australian Learning and Teaching Council, 2010)
The Learning and Teaching Academic Standards Statement for History is intended to offer a succinct description of the nature and extent of the discipline and to distinguish the threshold, ie minimum, level of achievement that can be expected of an Australian bachelor level graduate with a major in History. The Statement also sets out careers History graduates might pursue